UreR, the Transcriptional Activator of the Proteus mirabilis Urease Gene Cluster, Is Required for Urease Activity and Virulence in Experimental Urinary Tract Infections - Dattelbaum, Jonathan D. (American Society for Microbiology, 2003)
Proteus mirabilis, a cause of complicated urinary tract infection, produces urease, an essential virulence factor for this species. UreR, a member of the AraC/XylS family of transcriptional regulators, positively activates expression of the ure gene cluster in the presence of urea. To specifically evaluate the contribution of UreR to urease activity and virulence in the urinary tract, a ureR mutation was introduced into P. mirabilis HI4320 by homologous recombination. The isogenic ureR::aphA mutant, deficient in UreR production, lacked measurable urease activity. Expression was not detected in the UreR-deficient strain by Western blotting with monoclonal antibodies raised against UreD. Urease activity and UreD expression were restored by complementation of the mutant strain with ureR expressed from a low-copy-number plasmid. Virulence was assessed by transurethral cochallenge of CBA mice with wild-type and mutant strains. The isogenic ureR::aphA mutant of HI4320 was outcompeted in the urine (P = 0.004), bladder (P = 0.016), and kidneys (P ≤ 0.001) 7 days after inoculation. Thus, UreR is required for basal urease activity in the absence of urea, for induction of urease by urea, and for virulence of P. mirabilis in the urinary tract.